Immunogenicity and efficacy of Ad26.COV2.S: An adenoviral vector–based COVID‐19 vaccine. Issue 1 (11th June 2022) - Le Gars, Mathieu; Hendriks, Jenny; Sadoff, Jerald; Ryser, Martin; Struyf, Frank; Douoguih, Macaya; Schuitemaker, Hanneke
Abstract: Since its emergence in late 2019, the coronavirus disease 2019 (COVID‐19) pandemic has caused substantial morbidity and mortality. Despite the availability of efficacious vaccines, new variants with reduced sensitivity to vaccine‐induced protection are a troubling new reality. The Ad26.COV2.S vaccine is a recombinant, replication‐incompetent human adenovirus type 26 vector encoding a full‐length, membrane‐bound severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein in a prefusion‐stabilized conformation. This review discusses the immunogenicity and efficacy of Ad26.COV2.S as a single‐dose primary vaccination and as a homologous or heterologous booster vaccination. Ad26.COV2.S elicits broad humoral and cellular immune responses, which are associated with protective efficacy/effectiveness against SARS‐CoV‐2 infection, moderate to severe/critical COVID‐19, and COVID‐19–related hospitalization and death, including against emerging SARS‐CoV‐2 variants. The humoral immune responses elicited by Ad26.COV2.S vaccination are durable, continue to increase for at least 2‐3 months postvaccination, and involve a range of functional antibodies. Ad26.COV2.S given as a heterologous booster to mRNA vaccine–primed individuals markedly increases humoral and cellular immune responses. The use of Ad26.COV2.S as primary vaccination and as part of booster regimens is supporting the ongoing efforts to control and mitigate the COVID‐19 pandemic.